FRI0395 Incidence of myositis-specific autoantibody (MSA) specificities in sera referred to new zealand (NZ) medical laboratories. (15th June 2017) - O'donnell, J; Keating, P; Voorthuizen, M van; Liu, J; Chua, I; Soepnel, A; Gumbley, E; Spellerberg, M
Abstract : Background: Idiopathic inflammatory myopathies can be classified by clinicopathological phenotype into four major groups: overlap myositis (OM), dermatomyositis (DM), immune mediated necrotising myositis (IMMNM) and inclusion body myositis (IBM). The different phenotypes associate with distinct MSA specificities although a variable percentage within each group are seronegative and the majority of IBM patients are seronegative 1 . No commercial assay for the IBM associated specificity, cN1A, is available. In NZ testing for MSA is restricted to two laboratories: Waikato Hospital (WHL) and Canterbury Health Laboratories (CHL). Both laboratories use the commercial Euroimmun Euroline assay. In addition CHL has developed an ELISA for anti HMGCR autoantibodies and receives referrals from throughout NZ. Objectives: To define the incidence and specificities of MSA in serum samples referred for testing in New Zealand. Methods: For the period 3 November 2015 to 2 November 2016 each laboratory information system (LIS) was interrogated for requests for MSA. For the purposes of this report positive results were grouped into the specificities associated with each of the defined clinicopathological phenotypes. DM: Mi2, Tif-γ, MDA 5 NXP2 SAE1 OM: Ku, PM-Scl-100, PL75, Jo1, PL-7, PL-12, EJ, OJ IMMNM: HMGCR, SRP Results: Of screened sera (n=793, CHL=622, WHL=171) 11% were positive for MSA (88/793). Positive sera where distributed amongst three clinicopathological associated autoantibody specificities: DM 23% OM 50%, IMMNM 27%. The most common serum specificities were HMGCR (n=24) and Jo-1 (n=13). No serum with specificities to SRP or OJ was detected. 22/24 sera positive for anti HMGCR had an elevated CPK concentration (CPK>2500u/l in 21/24 and CPK=544 in 1/24, reference range =66–220). Conclusions: In New Zealand 11% of sera referred for MSA testing were positive. As a group the most common specificities were those associated with OM while the most common antigen specificity was to HMGCR. Anti-HMGCR antibodies were almost invariably associated with major elevations in serum CPK. References: Beveniste O, Stenzel W, Allenbach Y. Advances in serological diagnostics of inflammatory myopathies. Curr Opin Neurol 2016;29:662–673. Disclosure of Interest: None declared